2015
DOI: 10.1097/meg.0000000000000419
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for bleeding evaluated using the Forrest classification in Japanese patients after endoscopic submucosal dissection for early gastric neoplasm

Abstract: Hemodialysis is a risk factor for post-ESD bleeding. Proper classification of exposed vessels within post-ESD ulcers according to the Forrest classification using second-look endoscopy might help predict or prevent recurrent bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 50 publications
1
13
1
1
Order By: Relevance
“…Table shows the endoscopic findings on second‐look endoscopy according to the Forrest classification after ESD in our study and recent studies . These studies were carried out on patients with an average risk of post‐ESD bleeding and were not aimed at high‐risk patients.…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…Table shows the endoscopic findings on second‐look endoscopy according to the Forrest classification after ESD in our study and recent studies . These studies were carried out on patients with an average risk of post‐ESD bleeding and were not aimed at high‐risk patients.…”
Section: Resultsmentioning
confidence: 88%
“…These studies were carried out on patients with an average risk of post‐ESD bleeding and were not aimed at high‐risk patients. Five prospective studies showed that the proportion of Forrest classification Ia, Ib, and IIa lesions ranged from 15.1% to 64.2%. The proportion of actively bleeding lesions (Forrest Ia and Ib) in previous studies ranged from 9.6% to 14.0% .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations